Учебник немецкого языка - Агаркова Н. А. Наталия Алексеевна; Волявская Б. С. Белла Семеновна; Спивак Л. Н. Любовь Наумовна; Тарановская Н. М. Наталия Михайловна (Киев, Вища школа, 1970)
Исключено из фонда НТБ ТПУ